Barriers and facilitators to the implementation of a national multisectoral action plan for the prevention and control of noncommunicable diseases in Nepal: perspectives of stakeholders. Issue 1 (1st January 2021) - Dhimal, Meghnath; Dhimal, Mandira Lamichhane; Dahal, Sushma; Shrestha, Mahendra Prasad; Gyanwali, Pradip; Shao, Ruitai; Mikkelsen, Bente; Wickramasinghe, Kremlin; Marten, Robert; Jha, Anjani Kumar; Townsend, Nick
ABSTRACT: Background: Nepal adopted the Multisectoral Action Plan for the Prevention and Control of Non-Communicable Diseases (MSAP) in 2014. Implementation of the plan has been challenging, with limited participation from non-health sectors. Objectives: The overall aim of the study was to gain the perspectives of key stakeholders involved in the Nepal MSAP on the barriers and facilitators to its implementation, through the participation of relevant sectors in the plan. Methods: We held face-to-face semi-structured interviews with 12 stakeholders working in sectors involved in the MSAP. These sectors included the Office of the Prime Minister and Council of Ministries; Ministry of Health and Population (MOHP); Ministry of Education, Science and Technology; Ministry of Forest and Environment; academia; and professional organizations. Thematic analysis of transcripts was used to identify themes on awareness of NCDs, awareness of the MSAP, and barriers and facilitators to participation in the MSAP. Results: Participants recognised NCDs as a growing and major burden in Nepal. However, a number of participants were not familiar with the MSAP, identifying a lack of leadership and poor dissemination. Political and systemic transformation, since the adoption of the MSAP, was seen as a key barrier to implementation. International commitments to develop multisectoral action made by the Government of Nepal were identified as drivers. The recent establishment of a separate section for NCDs and Mental Health within the Department of Health Services of MOHP and the promotion of a Health in All Policies (HiAP) approach in recent national documents, were both considered to support implementation. Conclusions: The establishment of permanent multisectoral or multistakeholder mechanisms has been challenging despite strong political calls for their development. Moving beyond 2020, multisectoral action plans should engage with stakeholders from federal, provincial and local governments in order to develop costed action plans with specific roles and responsibilities for each sector.